Resumption of Cyclic Ovarian Activity by Herbal Preparation AyuFertin in Bulgarian Murrah Buffaloes at Early Postpartum - Yordanka Ilieva; Nasko Vasilev; Ivan Fasulkov; Pencho Penchev; Desislava Abadjieva; Vanya Mladenova; Ayla Ilyazova; Dasha Mihaylova; Stanimir Yotov; Elena Kistanova (Animals, 2021)
This study evaluates the phytochemical composition and ability of herbal preparation AyuFertin, supplemented shortly after calving, to resume the cyclic ovarian activity in postpartum Bulgarian Murrah buffaloes. In total, 13 healthy Bulgarian Murrah buffaloes at the age of 4–10 years, calved in March–April 2019 were involved in the experiment. Seven experimental buffaloes were treated individually per os with AyuFertin according to producer instruction. All animals were subjected to regular ultrasound examination of ovaries. GC-MS analysis of fatty acids composition and HPLC-DAD analysis of carotenoid and tocopherol content in AyuFertin were conducted. The determination of estrus occurrence and natural mating were done by a fertile bull. The development of the large follicles (12.5–14.3 mm) in 85.7% of treated animals was observed on day 24 postpartum compared to 0% in controls. Clinical signs of estrus were recorded in 71.4% of the animals, followed by an 80% pregnancy rate versus 16% in controls within 70 days after calving. In conclusion, the supplementation of the bioactive herbal product AyuFertin from day 21 postpartum can stimulate the follicular growth in the buffalo’s ovary, which leads to the development of follicles with ovulatory capacity, followed by successful ovulation. The above-mentioned treatment resulted in a better pregnancy rate in the treated multiparous compared to the control buffaloes bred by natural service.